Slang Words Found in Hidden Figure Movie - Kalakmabin , Yemeliana Ovince (Institut Pariwisata dan Bisnis Internasional, 2023)
This study deals with slang words found in Hidden Figure movie. This research attempts to find out the types of slang and the characteristics of slang words in Hidden Figure movie. The theory proposed by Chapman (1988) was used to find the types of slang and the theory from Sumarsono (2007) was used to analysis the characteristics of slang words. The documentation method was used to collect the data by taking advantage of the picture, note taking, and recording. Regarding to the first objective, there are two types of slang words found in this movies, such as primary slang and secondary slang. The occurrence of primary slang dominates the slang type used in this movie, since the speaker can make this slang type is easily understood by people. Referring to the second object, there are six characteristics of slang words found in this movie, which are clipping, creative, metathesis, acronym, use new existing words and metaphor, but the most ones used are clipping, creative, acronym, new existing words and metaphor. Therefore, the mostly characteristics used is use new existing words.